Polymorphism in LEP and LEPR May Modify Leptin Levels and Represent Risk Factors for Thyroid Cancer - Marjory Alana Marcello; Antonio Ramos Calixto; Jacqueline Fatima Martins de Almeida; Mariana Bonjiorno Martins; Lucas Leite Cunha; Camila Ayume Amano Cavalari; Elba C. S. Etchebehere; Ligia Vera Montalli da Assumpção; Bruno Geloneze; Andre Lopes Carvalho; Laura Sterian Ward (International Journal of Endocrinology)
Purpose. To understand the role of polymorphisms in the LEP (rs7799039 and rs2167270) and LEPR (rs1137101 and rs1137100) genes in DTC susceptibility and their effect on leptin levels. Methods. We studied 153 patients with DTC and 234 controls through TaqMan SNP Genotyping and ELISA, comparing these data to the clinicopathological data of patients with DTC. Results. Patients with AA genotype of rs7799039 had higher levels of serum leptin (9.22±0.98 ng/mL) than those with AG genotype (10.07±0.60 ng/mL; P=0.005). Individuals with AG genotype of rs2167270 also produced higher serum leptin levels (10.05±0.59 ng/mL) than the subjects with GG genotype (9.52±0.79 ng/mL; P<0.05). A multivariate logistic regression adjusted for gender, age, and BMI showed that the AG genotype of rs7799039 was an independent risk for DTC (OR, 11.689; P=0.0183; 95% CI, 1.516–90.119). Similarly, AG and GG genotypes of rs1137101 increased the susceptibility to DTC (OR, 3.747; P=0.027; 95% CI, 1.161–12.092 and OR, 5.437; P=0.013; 95% CI, 1.426–20.729). Conclusions. We demonstrated that rs7799039 and rs2167270 polymorphisms modify the serum leptin concentrations in patients with DTC. Furthermore, polymorphisms rs7799039 and rs1137101 increase the risk of DTC development, although they do not correlate with tumor aggressiveness.